THE CORRELATION BETWEEN READING STRATEGIES AND LEARNING ACHIEVEMENT - Ahmad Mahfudillah Syam (Language-Edu, 2021)
AbstractReading strategies are an important thing that should be known by the learners in order to enhance their learning achievement. Strategy is not only supporting the learners to improve their learning achievement, but also it can make the learners easy in comprehending the reading text. Hence, this study underlined in the case whether the strategies correlate with reading achievement. The participants were 28 English department college students who is in 4rd grade semester. In this class, there are 9 males and 19 females. In collecting data, the researcher administered two instruments, such as questionnaire and reading test. The result of this study showed that the correlation coefficient between robtained was lower than rtable. Then, the level of probability (p) Sig. (2-tailed) was 0.410 which was higher than 0.05. It means that H0 was accepted and Ha was rejected. Hence, it can be concluded that there was no correlation indicated that metacognitive reading strategy and student’s reading achievement associated each other.Key Words: Reading strategy, students’ learning achievement, correlation study